Calcium-sensing receptors promoted Homer1 expression and osteogenic differentiation in bone marrow mesenchymal stem cells - Liu Kainan; Xu Tianjie; Fan Jiaxin; Li Yueyuan; Guo Xiaoling; Zhang Hui; Wang Qian (Open Life Sciences, 2025)
Homer1 interacts with calcium-sensing receptors (CaSRs) in osteoblasts (OBs), with both CaSR and Homer1 playing essential roles in AKT phosphorylation. This study investigated the impact of CaSR on Homer1 expression during the differentiation of rat bone marrow mesenchymal stem cells (BMSCs) at morphological, imaging, and molecular levels, both in vivo and in vitro. A post-oophorectomy osteoporosis model was established in Sprague-Dawley rats, validated through micro-computed tomography, hematoxylin-eosin staining, and biomechanical testing to assess in vivo changes in CaSR expression. BMSCs were isolated from 3 week-old SD rats for in vitro OB differentiation studies, wherein osteogenic differentiation was induced alongside changes in CaSR expression. Morphological alterations were examined using transmission electron microscopy and immunofluorescence staining. Furthermore, the protein and mRNA levels of OB-specific genes were quantified by Western blot and reverse transcription quantitative real-time polymerase chain reaction, with Homer1-related proteins also assessed. Results showed a reduction in CaSR and Homer1 expression in the ovariectomized group. In cellular studies, CaSR activation upregulated AKT, Homer1, and osteogenic markers, promoting cell differentiation. In conclusion, CaSR enhances OB differentiation, likely via Homer1-mediated regulation of AKT signaling, suggesting CaSR as a potential therapeutic target for osteoporosis.